Simulating the fate and transport of salinity species in a semi-arid agricultural groundwater system: model development and application - Tavakoli Kivi, Saman, author; Bailey, Ryan T., advisor; Gates, Timothy K., advisor; Ronayne, Michael J., committee member; Bhaskar, Aditi, committee member (Colorado State University. Libraries, 2018)
Many irrigated agricultural areas worldwide suffer from salinization of soil, groundwater, and nearby river systems. Increased salinity concentrations, which can lead to decreased crop yield, are due principally to the presence of salt minerals and high rates of evapotranspiration. High groundwater salt loading to nearby river systems also affects downstream areas when saline river water is diverted for additional uses. Irrigation-induced salinity is the principal water quality problem in the semi-arid region of the western United States due to the extensive background quantities of salt in rocks and soils. Due to the importance of the problem and the complex hydro-chemical processes involved in salinity fate and transport, a physically-based spatially-distributed numerical model is needed to assess soil and groundwater salinity at the regional scale. Although several salinity transport models have been developed in recent decades, these models focus on salt species at the small scale (i.e. soil profile or field), and no attempts thus far have been made at simulating the fate, storage, and transport of individual interacting salt ions at the regional scale within a river basin. The required model must be able to handle variably-saturated groundwater systems; sources and sinks of groundwater within an agricultural system such as canal seepage, infiltrated water from flood and sprinkler irrigation, groundwater pumping, and evapotranspiration from both the unsaturated and shallow saturated zones; root zone processes such as salt ions cycling, crop uptake, and leaching to the water table; addition of salt mass via fertilizer and irrigation water; chemical kinetics affecting salt ions such as the influence of dissolved oxygen and nitrate on the chemical processes of anions such as sulfate (SO4); and equilibrium chemistry processes such as precipitation-dissolution, complexation, and cation exchange. This dissertation develops a physically-based, spatially-distributed groundwater reactive transport model that simulates the fate and transport of major salt ions in an agricultural groundwater system and can be applied to regional scale areas to address salinity problems. The model is developed by 1) constructing an equilibrium chemistry model that includes all the fate and transport processes that affect salt ions in an agricultural soil-groundwater system, including precipitation-dissolution of salt minerals, ions complexation, and cation exchange; and 2) coupling the module with UZF-RT3D (Bailey et al., 2013) a MODFLOW-based numerical modeling code that simulates the transport of multiple interacting reactive solutes in a variably-saturated soil-groundwater system. The model accounts for dissolved oxygen, nitrogen cycling in the soil-plant system (crop uptake, organic matter decomposition, mineralization/immobilization), oxidation-reduction reactions, including chemical reduction of dissolved oxygen and nitrate in the presence of marine shale, and sorption. UZF-RT3D has been amended to also include processes that directly affect SO4, one of the major salt ions, such as sulfur cycling in the plant-soil system and the release of SO4 from pyrite (FeS2)-laden marine shale in the presence of dissolved oxygen and nitrate. The developed model is applied to a salinity-affected irrigated alluvial stream-aquifer region to demonstrate its applicability and to assess remediation strategies on soil and groundwater salinity, salt mass loading to streams, and crop yield. The study area is a 500 km2 region of the Lower Arkansas River Valley (LARV) in southeastern Colorado, with the model tested against an extensive set of field data (soil salinity, groundwater salinity, salt loading from the aquifer to the Arkansas River) for the years 2006-2009. Parameter estimation is accomplished via a mixed manual-automated method, with estimation of both equilibrium and kinetic chemical parameters. Research results are presented through published and submitted articles. Results of preliminary best management practice (BMP) scenario testing indicates that reducing the volume of applied irrigation water and sealing earthen irrigation canals can have a significant effect on the root zone salinity, groundwater salinity, groundwater salt loading from the aquifer to the river network, and crop yield.
Keywords: groundwater; precipitation/dissolution; salinity; irrigation; equilibrium chemistry; reactive transport model